A review of metal recovery from spent petroleum catalysts and ash. (November 2015) - Akcil, Ata; Vegliò, Francesco; Ferella, Francesco; Okudan, Mediha Demet; Tuncuk, Aysenur
Highlights: Spent catalysts and ashes cause environmental risks due to their hazardous content. Valorization of the petrochemical waste would decrease the consumption of primary resources. Recovery of metals from catalysts and ashes have gained importance. Recovering metals from petrochemical waste would promote recycling culture. An overview on patented and commercial processes was also discussed. Abstract: With the increase in environmental awareness, the disposal of any form of hazardous waste has become a great concern for the industrial sector. Spent catalysts contribute to a significant amount of the solid waste generated by the petrochemical and petroleum refining industry. Hydro-cracking and hydrodesulfurization (HDS) catalysts are extensively used in the petroleum refining and petrochemical industries. The catalysts used in the refining processes lose their effectiveness over time. When the activity of catalysts decline below the acceptable level, they are usually regenerated and reused but regeneration is not possible every time. Recycling of some industrial waste containing base metals (such as V, Ni, Co, Mo) is estimated as an economical opportunity in the exploitation of these wastes. Alkali roasted catalysts can be leached in water to get the Mo and V in solution (in which temperature plays an important role during leaching). Several techniques are possible to separate the different metals, among those selective precipitation and solvent extraction are the most used. Pyrometallurgical treatment and bio-hydrometallurgical leaching were also proposed in the scientific literature but up to now they did not have any industrial application. An overview on patented and commercial processes was also presented.